An Algorithm to Process Signals Conveying Statistical Information - Rebollo Neira, Laura (1993)
A method for processing signals containing information about the state distribution of a physical system is presented. The concomitant algorithm is specifically devised to suitably adapt lineal restrictions so as to take into account the presence of noise due to experimental errors.